Efficacy of rusch intrauterine balloon in the management of postpartum haemorrhage – a practical review of a university hospital's experience. (18th April 2012) - Aojanepong, T; Naidu, M; Sheikh, S; Yu, C; Penna, L
Abstract : Objective: To review the use of Rusch intrauterine balloon catheter in the management of primary postpartum haemorrhage (PPH) to establish efficacy and to allow the development of practical recommendations to guide future use. Method: A retrospective study of women with primary PPH, who underwent a Rusch intrauterine balloon catheter insertion as part of management at Kings College Hospital between Jan 2009- Oct 2011. The need for additional surgical or medical interventions to control bleeding, the incidence of post-operative febrile morbidity (or suspected endometritis) and analgesia requirements were reviewed. Practical issues in relation to insertion and removal were compared to try to establish a common pathway for use. Results: 20 cases were reviewed. The Rusch intrauterine balloon catheter insertion is highly effective in controlling blood loss and thus reducing maternal morbidity by reducing the need for additional surgical intervention or blood transfusion. Febrile morbidity rates and analgesia requirements were low. The reviewed showed a wide variation in the approach to practical usage between clinicians. Conclusions: Rusch intrauterine balloon catheter insertion is a simple and effective method of managing women with failed medical management of PPH. A set of guidelines for practical usage is presented.